How do you solve y=-6x-3 and y=3 using the substitution method? Algebra Systems of Equations and Inequalities Systems Using Substitution 1 Answer Valerie ยท Stefan V. Apr 11, 2018 x=-1 y=3 Explanation: y= -6x-3 y=3 Because of the transitive property... -6x-3=3 Add 3 to both sides... -6x=6 Divide both sides by -6 x=-1 Answer link Related questions How do you solve systems of equations using the substitution method? How do you check your solutions to a systems of equations using the substitution method? When is the substitution method easier to use? How do you know if a solution is "no solution" or "infinite" when using the substitution method? How do you solve 12y-3x=-1 and x-4y=1 using the substitution method? Which method do you use to solve the system of equations y=1/4x-14 and y=19/8x+7? What are the 2 numbers if the sum is 70 and they differ by 11? How do you solve x+y=5 and 3x+y=15 using the substitution method? What is the point of intersection of the lines x+2y=4 and -x-3y=-7? How do you solve x-5y=15 and 4x-3y=26 using substitution? See all questions in Systems Using Substitution Impact of this question 10913 views around the world You can reuse this answer Creative Commons License